Periodontal medicine: The emergence of a new branch in periodontology - Pejčić Ana S.; Mirković Dimitrije S.; Obradović Radmila R.; Bradić Marija B.; Minić Ivan Z. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2016)
Introduction: Periodontal medicine is the emergence of a new branch of periodontology. Periodontal medicine is a term used for different purposes in different parts of the world. In certain countries, it relates to the study of the dynamic relationship between periodontal diseases and systemic conditions, such as cardiovascular and cerebrovascular disease, preterm delivery low-birth-weight babies, diabetes mellitus, osteoporosis, and disorders of the respiratory tract. Such studies investigate the peripheral impacts of periodontal inflammation on systemic health. In other countries, 'periodontal medicine' is a term used to describe the periodontal (and gingival) manifestations of medical conditions. This includes their investigation, diagnosis and therapeutic management and how management of the oral condition integrates with the patient's medical management as part of a holistic approach within defined care pathways. Conclusion: The text is a comprehensive analysis of research on periodontal disease and its link to systemic conditions. The periodontal treatment may be important in terms of preventing a patient's overall health. Periodontologists emphasize that infections in the mouth can cause health problems in other parts of the body.